Stage two milk fever in a dairy cow: a case report - Abdullah, Faez Firdaus Jesse; Osman, Abdinasir Yusuf; Abba, Yusuf; Adamu, Lawan; Mohammed, Konto; Tijjani, Abdulnasir; Mauli, Anis Athira; Saharee, Abdul Aziz; Haron, Abdul Wahid (International Organization of Scientific Research, 2014)
The biological cycles of milk production and reproduction determine dairy profitability thus making management decisions dynamic and time-dependent. Metabolic diseases pose significant risk on net earnings of a dairy enterprise. We report a case of clinical hypocalcaemia (milk fever). A 7-year-old Jersey cross cow weighing 500 kg was presented with left lateral recumbency with the neck curved towards the flank. The case history indicated that the animal had calved two months ago and was semi-intensively managed. There was no history of vaccination and deworming. The daily production of milk was about 13 liters.